Efficacy analysis of minimally invasive treatment for scapular coracoid fractures assisted by TiRobot ForcePro Superior - Zhiyun, Tan; Yonghong, Dai; Qingyu, Li; Yanhui, Zeng; Kuangyang, Yang; Xing, Chen (Frontiers in Surgery, 2025)
BackgroundAccurate spatial positioning is the key to the precise implantation of coracoid screws. This study aimed to explore the efficacy and current issues of TiRobot ForcePro Superior (TFS) in the treatment of scapular coracoid fractures by comparing it with the freehand screw implantation technique.MethodsA retrospective analysis was conducted on the medical records of 29 patients with scapular coracoid fractures who underwent surgical treatment at Foshan Hospital of Traditional Chinese Medicine from 2019 to 2024. Based on the surgical approach, the patients were divided into the robot-assisted group (n = 15) and the control group (n = 14). In the robot-assisted group, the TFS system was utilized to plan the optimal screw trajectory, and the surgeon implanted the guide pin along the mechanical arm sleeve of the TFS, followed by precise screw placement along the guide pin to fix the coracoid fracture. In the control group, screws were implanted freehand by the surgeon.ResultsThe intraoperative blood loss and incision length in the robot-assisted group were significantly less than those in the control group. The visual analog scale (VAS) pain scores in the robot-assisted group were significantly lower than those in the control group. The shoulder function scores in the robot-assisted group were significantly higher than those in the control group. No statistically significant differences were observed between the two groups in terms of operative time, hospital stay, screw placement accuracy, incidence of postoperative complications, or fracture healing time.ConclusionCompared with freehand screw implantation, minimally invasive treatment for scapular coracoid fractures assisted by TFS significantly reduced intraoperative blood loss, shortened incision length, alleviated pain, and better promoted the recovery of shoulder joint function.